Development to term of cloned cattle derived from donor cells treated with valproic acid. - Juliano Rodrigues Sangalli (Public Library of Science (PLoS), 2014)
Cloning of mammals by somatic cell nuclear transfer (SCNT) is still plagued by low efficiency. The epigenetic modifications established during cellular differentiation are a major factor determining this low efficiency as they act as epigenetic barriers restricting reprogramming of somatic nuclei. In this regard, most factors that promote chromatin decondensation, including histone deacetylase inhibitors (HDACis), have been found to increase nuclear reprogramming efficiency, making their use common to improve SCNT rates. Herein we used valproic acid (VPA) in SCNT to test whether the treatment of nuclear donor cells with this HDACi improves pre- and post-implantation development of cloned cattle. We found that the treatment of fibroblasts with VPA increased histone acetylation without affecting DNA methylation. Moreover, the treatment with VPA resulted in increased expression of IGF2R and PPARGC1A, but not of POU5F1. However, when treated cells were used as nuclear donors no difference of histone acetylation was found after oocyte reconstruction compared to the use of untreated cells. Moreover, shortly after artificial activation the histone acetylation levels were decreased in the embryos produced with VPA-treated cells. With respect to developmental rates, the use of treated cells as donors resulted in no difference during pre- and post-implantation development. In total, five clones developed to term; three produced with untreated cells and two with VPA-treated cells. Among the calves from treated group, one stillborn calf was delivered at day 270 of gestation whereas the other one was delivered at term but died shortly after birth. Among the calves from the control group, one died seven days after birth whereas the other two are still alive and healthy. Altogether, these results show that in spite of the alterations in fibroblasts resulting from the treatment with VPA, their use as donor cells in SCNT did not improve pre- and post-implantation development of cloned cattle.